DILEMA ERA DIGITAL : DAMPAK POSITIF DAN NEGATIF MEDIA SOSIAL TERHADAP PROSES SOSIALISASI ANAK SEKOLAH DASAR - Masykuria Luthfia Ananda; Jeny Talia; Hanum Salsa Bella (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Technology has become an inseparable part of life, including in the world of education. Although technology, especially social media, offers positive benefits, it also carries negative risks. In the digital era, social media is used by various groups, including elementary school children, to interact and learn. Social media such as YouTube, Google, etc., have influenced the way children socialize. This research aims to discuss the impact of social media on the socialization of elementary school children, both positive and negative, as well as looking for ways to maximize the benefits and reduce the negative impacts. The method used is descriptive qualitative research with literature study. Data is collected from books, journals, and others. Social media has a significant impact on the way elementary school children socialize and communicate. Although it offers benefits such as increased technological skills and socialization, social media also carries negative risks that need to be addressed through proper supervision and guidance. In this way, the negative impact of social media on children's socialization in elementary school can be minimized, while the positive benefits can be maximized.